Tuning Down the Pain – An Overview of Allosteric Modulation of Opioid Receptors: Mechanisms of Modulation, Allosteric Sites, Modulator Syntheses - Bartuzi, Damian; Wr, Tomasz M.; Kaczor, Agnieszka A.; Matosiuk, Dariusz (Current Topics in Medicinal Chemistry, 2020)
Opioid signaling plays a central role in pain perception. As such, it remains the main target in the development of antinociceptive agents, despite serious side effects involved. In recent years, hopes for improved opioid painkillers are rising, together with our understanding of allosterism and biased signaling mechanisms. In this review, we focus on recently discovered allosteric modulators of opioid receptors, insights into phenomena underlying their action, as well as on how they extend our understanding of mechanisms of previously known compounds. A brief overlook of their synthesis is also presented.
Keywords: GPCRs